Pengaruh Paparan Gelombang Ultrasonik pada Ekstraksi Bunga Telang Terhadap Kandungan Senyawa Flavonoid - Bilqis Widiawati, Febriana; Mustikaningrum, Mega (SURYA TEKNIKA, 2025)
The study aims to determine the effect of ultrasonic wave exposure on the extraction of butterfly pea flowers (Clitoria ternatea L.) toward flavonoid compound content. The method used was Ultrasonic Assisted Extraction (UAE) with variations in temperature 30oC, 40oC, 50oC, extraction time 20, 25, 30 minutes, and ethanol solvent volume 50, 100, 150 ml. analysis was carried out using a UV-Vis Spectrophotometer. The results showed that the optimal extraction time was 25 minutes with a yield of 45,51%, the optimal temperature was 40oC with a yield of 24,6%, and optimal solvent volume was 100 ml with a yield of 43,05%. Kinetic analysis indicated that the Pseudo Second Order model was the most suitable with a regression value of 0,99989. The extraction process was dominatetd by physical diffusion with an activation energy of 8,4621 kJ/mol, indicating that increasing temperature enhances extraction rate without significant degradation of active compounds.